Penerapan Model Joyful Learning untuk Meningkatkan Minat Belajar - Ngatun Lestari; Hari Sunaryo; Ismeini Tri Nugraheni; Desi Murtofiah; Mohtar Al Dadik; Muhammad Adi Kurniawan (KAMPUS AKADEMIK PUBLISING, 2026)
Student interest in learning is a crucial factor in the educational process, and the Joyful Learning model effectively fosters this interest through a pleasant atmosphere. This study aims to describe the steps, advantages, and disadvantages of applying the Joyful Learning model in learning at Madrasah Tsanawiyah Negeri 3 Sukoharjo, Madrasah Tsanawiyah Negeri 11 Boyolali, Madrasah Aliyah Negeri Temanggung, Madrasah Aliyah Negeri Sukoharjo, and Madrasah Aliyah Negeri 1 Magelang. Using a descriptive qualitative approach, the research subjects were teachers as the main informants, with data collection techniques through interviews, observation, and documentation. The results show that the Joyful Learning steps include the preparation stage (stimulating student readiness), delivery (relating the material to real life), training (core learning activities with feedback), and closing (reinforcing the material). The advantages include a relaxed atmosphere, variety of strategies, and increased student creativity; while the disadvantages are the risk of uncontrolled classes, the demand for mastery of various methods, and the need for high teacher creativity. In conclusion, the Joyful Learning model is suitable for increasing learning interest in madrasahs.